2010
DOI: 10.1007/s10562-010-0352-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Cyclohexane by Oxygen in a Solvent-Free System over Lanthanide-Containing AlPO-5

Abstract: Ln-containing AlPO-5 (Ln = La, Ce, Sm, Dy, Y, Gd) were synthesized hydrothermally in the presence of HF, and characterized by XRD, UV-vis, SEM, N 2 adsorption/desorption, FT-IR, solid state 27 Al MAS NMR and ICP-AES techniques. The results showed that all the samples had good crystallinity and high specific area. Isomorphous substitution of Ln ions for Al ?3 occurred. The lanthanide ions were incorporated into the frameworks or were highly dispersed on extra frameworks of the samples. The newly synthesized cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
(64 reference statements)
5
20
0
Order By: Relevance
“…The patterns exhibited the characteristic reflections of AlPO-5. 16 There are no extra peaks other than the peaks corresponding to AlPO-5, thus confirmed the absence of free ceria phase in CeAlPO-5. On comparison of the patterns of AlPO-5 and CeAlPO-5, the 2 values were shifted and the lattice parameters were changed which supported framework substitution of cerium.…”
Section: Xrdsupporting
confidence: 53%
“…The patterns exhibited the characteristic reflections of AlPO-5. 16 There are no extra peaks other than the peaks corresponding to AlPO-5, thus confirmed the absence of free ceria phase in CeAlPO-5. On comparison of the patterns of AlPO-5 and CeAlPO-5, the 2 values were shifted and the lattice parameters were changed which supported framework substitution of cerium.…”
Section: Xrdsupporting
confidence: 53%
“…UV/Vis spectra of LaAlPO‐5‐M samples with different ratios of Al/La are shown in Figure . The absorption peak at λ =256–300 nm (Figure a) for LaAlPO‐5‐M (Al/La=50) is assigned to four‐coordinate La III in the sample framework and six‐coordinated extra‐framework La species . The peak at λ ∼220 nm (assigned to La 2 O 3 ) can hardly be observed, which is in agreement with the XRD results.…”
Section: Resultsmentioning
confidence: 99%
“…Catalytic materials based on raree arths (RE) are used widely in the water gas shift, [34,35] oxidatived ehydrogenation, [36][37][38] aldol condensation, [39] and other reactions [40] because of their specific chemical properties. [41][42][43] We reported that Ce-doped AlPO-5 materials exhibit ah igh catalytic performance for the oxidation of cyclohexane [44,45] and the oxidation of styrene over La-MCM-48 [46] and Ln-MCM-41 (Ln = La, Ce, Sm, Yb) [47] catalysts. Herein, RE-doped mesoporous AlPO-5( LnAlPO-5-MAlPO-5-M) catalysts were prepareda nd used to catalyzeU llmann coupling reactions of phenols with nitro-substituted aryl halides in the absence of ligands for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…The pH decreased as a result of the dissolution of CO 2 in water and its partial ionization to form the acid. [34,35] Compared with AlPO-5, heteroatom-substituted mesoporous aluminophosphates generate catalytic redox or acid sites. A steep increase in the isotherms can be seen at relative pressures P/P 0 in the range of 0.4-1.0 in the samples of AlPO-5 synthesized in compressed CO 2 , which is characteristic of the presence of mesopores.…”
Section: Resultsmentioning
confidence: 99%